(untitled) (KYAMC Journal, 2013)
Introduction: Echocardiography is the definitive diagnostic tool for left ventricular systolic dysfunction. But it is expensive and requires trained manpower and thus might not be available in the primary care set up. EGG and Chest X ray, the more basic investigations, may help diagnose LVSD or at least streamline those who absolutely require echocardiography in primary care setup. Methods: ECG, Chest X ray and Echocardiography along with clinical assessment were performed on 70 patients with some form of complaints related to heart. The inferences on systolic function obtained from ECG, Chest X ray were compared with Echocardiography findings. Results: Out of 70 participants, 50 had left ventricular ejection fraction less than 45%, 56 had abnormal EGG, 60 had cardiomegaly in chest X-ray. A set of pre-selected ECG abnormalities had a sensitivity of 100% (83.4-100), specificity of 70% (35.4-91.9) and a positive predictive value of 89.3% (70.6-97.2) in diagnosing LVSD. Likewise, the figures were 92% (72.5-98.6), 30% (8.l-64.6) and 76.7% (57.3-89.4) respectively for a cardiothoracic ratio of more than 0.5 in chest X-ray. Conclusions: Although, ECG and Chest X-ray could not replace Echocardiography, they could very well give an idea of the systolic function of an individual and suggest the need or no need for an echo-study in primary care setup. DOI: http://dx.doi.org/10.3329/kyamcj.v2i1.13515 KYAMC Journal Vol.2(1) 2011 pp.118-122